2021
DOI: 10.36685/phi.v7i3.438
|View full text |Cite
|
Sign up to set email alerts
|

The perilous riding behavior and accident of motorcycles in university students

Abstract: Background: An inevitable traffic accident frequently resulted from the dereliction of individualized community from disobeying regulation which causes an impact on the safety of another person. The impact raised is not merely in terms of material but also non-material.Objective: This research was aimed to know the correlation between risky riding behavior and the accident of motorcycles experienced by university students of Halu Oleo University of Kendari, Indonesia.Methods: This research utilized the cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This reflects the common practice in Pakistan where males typically assume the role of motorcycle riders, while females tend to be passengers seated behind, influenced by social and cultural constraints. 10 Our study inferred those 48 (96%) patients had no driving license whereas 2(4%) patients had a driving license. Similar results were observed in another research by Muhammad et all, which concluded that the frequency of RTA is more common in drivers not having licenses as compared to license holders.…”
Section: Discussionmentioning
confidence: 60%
“…This reflects the common practice in Pakistan where males typically assume the role of motorcycle riders, while females tend to be passengers seated behind, influenced by social and cultural constraints. 10 Our study inferred those 48 (96%) patients had no driving license whereas 2(4%) patients had a driving license. Similar results were observed in another research by Muhammad et all, which concluded that the frequency of RTA is more common in drivers not having licenses as compared to license holders.…”
Section: Discussionmentioning
confidence: 60%
“…This is due to the high number of accidents involving students. 5 The number of motorcyclists in Indonesia is 81.78% of other types of vehicles. 8 Student experience is used as a measuring value to find out their attitudes and behaviors in using motorcycles on the road.…”
Section: Discussionmentioning
confidence: 99%
“…Unlikely ( 2) Possible ( 3) Likely ( 4) Certaint ( 5) Catastrophic (5) Low ( 5) Medium ( 10) High ( 15) High ( 20) High ( 25) Major ( 4) Low ( 4) Medium ( 8) Medium ( 12) High ( 16) High ( 20) Moderate (3) Low ( 3) Low ( 6) Medium ( 9) Medium ( 12) High ( 15) Minor ( 2) Low ( 2) Low ( 4) Low ( 6) Medium ( 8) Medium ( 10) Insignificant ( 1)…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Traffic accidents are a terrible scourge that occurs in many countries (Atmawati et al, 2021;Nancy, 2017). Especially in developing countries, where transportation matters such as tangled yarn (Aulia et al, 2020;Ningtyias et al, 2021;Prima et al, 2015).…”
Section: Introductionmentioning
confidence: 99%